Use of Python in the analysis of lexical availability - Pérez Durán, Marco Antonio (2026)
This paper describes the operationalization of López Chávez and Strassburger Frías' (2000) mathematical formula for lexical availability using the Python programming language. The methodology used is framed within a qualitative-explanatory approach of an illustrative nature, which allows us to observe how Python can be fully incorporated into lexical availability studies. Python significantly optimizes data processing, shortening the time required and facilitating analysis, as evidenced by the results.